Evaluation of Metro Fire Emergency Response Ability Based on WRSR. Issue 4 (April 2021) - Jiang, Xiaoshu; Dong, Sihui
Abstract: In order to clarify the status of subway fire emergency response capability, a comprehensive evaluation method based on the weighted rank-sum ratio method is proposed. Firstly, the factors affecting the emergency response capability of subway fire accidents was put forward on the basis of the current relevant laws and regulations, and a subway fire emergency response capability evaluation system was also built; secondly, the Analytic Network Process (ANP) was used to calculate the weight of each indicator in the system; then, the weighted rank sum ratio method (WRSR) is used to evaluate the overall status of the subway fire accident emergency response capability, and the sub-range of each subway emergency response capability is obtained; finally, model verification was conducted with 8 typical subways in Central China. The results show that C1, C3, C16, C20 and C29 constitute important indicators of subway fire emergency response capabilities; the constructed model can comprehensively evaluate the subway fire emergency response capabilities and facilitate its safety management.